HISTORICAL EMPATHY AND CANADA: A PEOPLE’S HISTORY - Bryant, Darren; Clark, Penney (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
In this article, we examine the CBC/Radio‐Canada series, Canada: A People’s History, for its use of empathy, specifically with regard to its portrayal of Aboriginal people. We call the empathy promoted in the series, emotive empathy, and compare it to the concept of historical empathy constructed by researchers in history education. The emotive empathy employed in this series, while adequate for public audiences, is not sufficient for history classrooms because it lacks a cognitive dimension. We discuss implications for using the series, and by extension, other instructional resources, to promote the development of historical empathy. Key Words: history teaching, historical empathy, history and film, narrative strategies, Aboriginal representations Dans cet article, les auteurs analysent le recours à l’empathie dans la série Le Canada : une histoire populaire / Canada: A People’s History de Radio‐Canada / CBC, surtout pour ce qui a trait à la représentation des autochtones. Les auteurs qualifient d’empathie émotive l’empathie promue dans la série et la compare au concept d’empathie historique développé par les chercheurs qui étudient l’enseignement de l’histoire. L’empathie émotive utilisée dans cette série, bien qu’adéquate pour le grand public, ne l’est pas pour les cours d’histoire parce qu’il manque alors une dimension cognitive. Les auteurs analysent les implications de l’utilisation de cette série et, d’une manière plus générale, d’autres ressources pédagogiques par rapport à la promotion de l’empathie historique. Mots clés : enseignement de l’histoire, empathie historique, histoire et films, stratégies narratives, représentation des autochtones